ANALISIS PELAKSANAAN CLINICAL PATHWAY DI RSUP PROF. DR. R. D. KANDOU MANADO - Paat, Cicilia; Kristanto, Erwin; Kalalo, Flora P. (UNIVERSITAS SAM RATULANGI, 2017)
Abstract: Clinical pathway is a significant administration document to achieve the good clinical governance in the hospital. In Indonesia, this document is one of the very critical requirements that should be provided by the hospital to fulfil the KARS 2012 policy. As the center of referral teaching hospital of East Indonesia, Professor Dr. R. D. Kandou General Hospital has committed to fulfil the international standard of care, inter alia implementation of the clinical pathways based on the main cause of death, high risk, and high cost. There are several obstacles concerning this implementation, such as the irresponsibility of the doctors due to overloaded work, lack of concentration in filling the formation of clinical pathway, and uncertainity in the usage of clinical pathway. This study was aimed to evaluate the implementation of the clinical pathway and its limitation in the hospital above. The results showed that the administrative policy of the clinical pathway had been provided by the top management leader with the specialization in dengue shock syndrome (DSS), chronic kidney disease (CKD), eclampsia, benign prostatic hypertrophy (BPH), and myocardial infarction (MCI) without complication. Conclusion: Clinical pathway was implemented at Prof. Dr. R. D. Kandou General Hospital according to the Minister Health Regulation No. 012 Year 2012 about Standard Accreditation for Hospital.Keywords: clinical pathway, hospitalAbstrak: Clinical pathway merupakan bagian penting dari dokumen dan alat dalam mewujudkan good clinical governance di rumah sakit. Di Indonesia, dokumen ini juga menjadi salah satu syarat yang harus dipenuhi dalam Standar Akreditasi Rumah Sakit versi KARS 2012. Rumah Sakit Prof. Dr. R. D. Kandou merupakan rumah sakit pendidikan dan pusat rujukan untuk wilayah Indonesia Timur, berkomitmen untuk meningkatkan pelayanan berstandar internasional; salah satu upayanya dengan mengimplementasikan clinical pathway. Pemilihan clinical pathway ditujukan pada penyakit-penyakit yang merupakan penyebab utama kematian, berisiko tinggi, dan biaya tinggi. Kendala penggunaan clinical pathway antara lain kurangnya kepatuhan dokter penanggung jawab pasien terhadap clinical pathway, kurangnya konsentrasi dalam pengisian pembentukan clinical pathway, serta kesulitan kepastian penggunaan clinical pathway. Penelitian ini bertujuan untuk mengetahui pelaksanaan clinical pathway dan analisis terhadap kendala-kendalanya di RSUP Prof. Dr. R. D. Kandou Manado. Hasil studi menunjukkan bahwa pada tingkat manajerial telah tersedia kebijakan clinical pathway dan spesialisasinya yaitu dengue shock syndrome (DSS), penyakit ginjal kronik (PGK), preeklamsia berat, benign prostat hypertrophy (BPH), dan miokard cardiac infark (MCI) tanpa komplikasi. Simpulan: Clinical pathway telah diterapkan di RSUP Prof. Dr. R. D. Kandou berdasarkan Permenkes Nomor 012 tahun 2012 tentang Standar Akreditasi Rumah Sakit.Kata kunci: clinical pathway, rumah sakit